Exosomal miR-483-5p in Bone Marrow Mesenchymal Stem Cells Promotes Malignant Progression of Multiple Myeloma by Targeting TIMP2 - Gu, Jianmei; Wang, Maoye; Wang, Xinfeng; Li, Jiao; Liu, Haiyan; Lin, Zenghua; Yang, Xi; Zhang, Xu; Liu, Hong (Frontiers in Cell and Developmental Biology, 2022)
Bone marrow-derived mesenchymal stem cell (BMSC) is one crucial component of the multiple myeloma (MM) microenvironment and supports the malignant progression of MM. Whether BMSCs act on MM cells via exosomes has not been well characterized. Herein, we used microarrays to screen out differentially expressed miRNAs in BMSCs from patients with MM (MM-MSCs) or benign diseases (BD-MSCs). We found that miR-483-5p was highly expressed in MM-MSCs, which may be transported through exosomes from MM-MSCs to MM cells to increase miR-483-5p expression in them. We then investigated the role and mechanism of miR-483-5p in the aggressive progression of MM in vitro. We verified that miR-483-5p promoted MM cell proliferation and reduced apoptosis. Then we predicted and validated that TIMP2, a tumor suppressor gene, is the downstream target of miR-483-5p in MM. In summary, our study indicated that MM-MSCs promote MM malignant progression via the release of exosomes and regulation of miR-483-5p/TIMP2 axis, suggesting an essential role of BMSCs derived exosomal miRNA in MM and a potential marker for MM diagnosis and therapy.